MR imaging features for improved diagnosis of hepatocellular carcinoma in the non-cirrhotic liver: Multi-center evaluation. Issue 10 (October 2015) - Fischer, M.A.; Raptis, D.A.; Donati, O.F.; Hunziker, R.; Schade, E.; Sotiropoulos, G.C.; McCall, J.; Bartlett, A.; Bachellier, Ph.; Frilling, A.; Breitenstein, S.; Clavien, P.-A.; et al.
Highlights: MR-Imaging characteristics of hepatocellular tumors in the non-cirrhotic liver show significant differences. Independent MRI-features of HCC are T1-hypointensity, T2-hypo-/hyperintensity, lack of central-enhancement, satellite-lesions and lack of liver specific contrast media uptake. Reproducibility and diagnostic performance of HCC specific features are good. Change of diagnostic paradigm has the potential to reduce unnecessary surgery. Abstract: Purpose: To determine MR-imaging features for the differentiation between hepatocellular carcinoma (HCC) and benign hepatocellular tumors in the non-cirrhotic liver. Material and Methods: 107 consecutive patients without liver cirrhosis (46 male; 45 ± 14 years) who underwent liver resection due to suspicion of HCC were included in this multi-center study. The following imaging features were assessed: lesion diameter and demarcation, satellite-lesions, central-scar, capsule, fat-content, hemorrhage, vein-infiltration and signal-intensity (SI) on native T1-, T2- and dynamic-enhanced T1-weighted images (center versus periphery). In addition, contrast-media (CM) uptake in the liver specific phase was analyzed in a sub-group of 42 patients. Results: Significant differences between HCC ( n  = 55) and benign lesions ( n  = 52) were shown for native T1-, T2- and dynamic-enhanced T1-SI, fat-content, and satellite-lesions (all, P  < .05). Independent predictors for HCC were T1-hypointensity (odds-ratio, 4.81), T2-hypo-/hyperintensity (5.07), lack of central tumor-enhancement (3.36), and satellite-lesions (5.78; all P  < 0.05). Sensitivity and specificity of HCC was 91% and 75% respectively for two out-of four independent predictors, whereas specificity reached 98% for all four predictors. Sub-analysis, showed significant differences in liver specific CM uptake between HCC ( n  = 18) and benign lesions ( n  = 24; P  < 0.001) and revealed lack of liver specific CM uptake (odds-ratio, 2.7) as additional independent feature for diagnosis of HCC. Conclusion: Independent MRI features indicating HCC are T1-hypointensity, T2-hypo- or hyperintensity, lack of central tumor-enhancement, presence of satellite-lesions and lack of liver specific CM-uptake. These features may have the potential to improve the diagnosis of HCC in the non-cirrhotic liver.